Pathophysiology made incredibly easy! - Scott, William N. (Made incredibly easy, 2012)
Suitable for nursing students and those studying on other Allied Health Professional fields, this title covers the relevant areas of pathophysiology. It focuses on UK related conditions, and includes chapters on reproductive diseases and complaints, and on skin